Highly Efficient Nonvolatile Magnetization Switching and Multi‐Level States by Current in Single Van der Waals Topological Ferromagnet Fe3GeTe2. (7th September 2021) - Zhang, Kaixuan; Lee, Youjin; Coak, Matthew J.; Kim, Junghyun; Son, Suhan; Hwang, Inho; Ko, Dong‐Su; Oh, Youngtek; Jeon, Insu; Kim, Dohun; Zeng, Changgan; Lee, Hyun‐Woo; et al.
Abstract: Robust multi‐level spin memory with the ability to write information electrically is a long‐sought capability in spintronics, with great promise for applications. Here, nonvolatile and highly energy‐efficient magnetization switching is achieved in a single‐material device formed of van‐der‐Waals (vdW) topological ferromagnet Fe3 GeTe2, whose magnetic information can be readily controlled by a tiny current. Furthermore, the switching current density and power dissipation are about 400 and 4000 times smaller than those of the existing spin‐orbit‐torque magnetic random access memory based on conventional magnet/heavy‐metal systems. Most importantly, multi‐level states, switched by electrical current are also demonstrated, which can dramatically enhance the information capacity density and reduce computing costs. Thus, the observations combine both high energy efficiency and large information capacity density in one device, showcasing the potential applications of the emerging field of vdW magnets in the field of spin memory and spintronics. Abstract : The highly energy‐efficient nonvolatile magnetization switching and multi‐level states by current are achieved in single van‐der‐Waals (vdW) topological ferromagnet Fe3 GeTe2 . The switching current density and power dissipation are about 400 and 4000 times smaller than conventional magnet/heavy‐metal‐based spin orbit torque magnetic random access memory. The observations combine high energy‐efficiency and large information‐capacity‐density in one device, bringing the nascent vdW magnets toward spin memory and spintronics.